Prosystemin, a prohormone that modulates plant defense barriers, is an intrinsically disordered protein. (5th December 2017) - Buonanno, Martina; Coppola, Mariangela; Di Lelio, Ilaria; Molisso, Donata; Leone, Marilisa; Pennacchio, Francesco; Langella, Emma; Rao, Rosa; Monti, Simona Maria
Abstract: Prosystemin, originally isolated from Lycopersicon esculentum, is a tomato pro‐hormone of 200 aminoacid residues which releases a bioactive peptide of 18 aminoacids called Systemin. This signaling peptide is involved in the activation of defense genes in solanaceous plants in response to herbivore feeding damage. Using biochemical, biophysical and bioinformatics approaches we characterized Prosystemin, showing that it is an intrinsically disordered protein possessing a few secondary structure elements within the sequence. Plant treatment with recombinant Prosystemin promotes early and late plant defense genes, which limit the development and survival of Spodoptera littoralis larvae fed with treated plants.